Red Stick Men: Stories - Parrish, Tim (University Press of Mississippi, 2000)
The characters in these stories "are always on the verge of disasters that emanate from the hard living they endure in the city they call 'Red Stick,'" i.e., Baton Rouge, Louisiana.–Jacket.
Keywords: Baton Rouge; Fiction; Fiction; Baton Rouge (La.); Louisiana; Oil industry workers; Social life and customs; dept.eng; faculty_collection